2002
DOI: 10.1007/s00216-002-1295-x
|View full text |Cite
|
Sign up to set email alerts
|

The application of ETAAS to the determination of Cr, Pb and Cd in samples taken during different stages of the winemaking process

Abstract: Chromium, cadmium and lead were determined in different fractions of the winemaking process such as in grape, pressed pomace, must deposit, deposit of lees, must and wine. Grape, pressed pomace, must deposit and deposit of lees were digested by a high-pressure microwave-assisted digestion system with a mixture of nitric acid and hydrogen peroxide, while for must and wine no special treatment was required. The temperature programs of the graphite furnace were optimised and different matrix modifiers were applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 10 publications
3
33
0
Order By: Relevance
“…Italian red wines (Marengo & Aceto 2003), Argentinian red and white wines (Lara et al 2005;Pohl 2007), Macedonian (Cvetkovi et al 2006), and Slovenian wines (Kristl et al 2002) had lower contents of cadmium than the studied Croatian wines. The cadmium concentration range for Hungarian wines (Pohl 2007) was wider than the concentration range established in this study.…”
Section: Mineral and Heavy Metals Contents In Blackberry Winesmentioning
confidence: 74%
“…Italian red wines (Marengo & Aceto 2003), Argentinian red and white wines (Lara et al 2005;Pohl 2007), Macedonian (Cvetkovi et al 2006), and Slovenian wines (Kristl et al 2002) had lower contents of cadmium than the studied Croatian wines. The cadmium concentration range for Hungarian wines (Pohl 2007) was wider than the concentration range established in this study.…”
Section: Mineral and Heavy Metals Contents In Blackberry Winesmentioning
confidence: 74%
“…Chemical modifiers used for thermal stabilization of Cd and Pb in wine samples are Pd(NO 3 ) 2 [17,28], Pd(NO 3 ) 2 +Mg (NO 3 ) 2 [27,29,31], NH 4 H 2 PO 4 [5,21,32], and NH 4 H 2 PO 4 +Mg(NO 3 ) 2 [29,30]. However, Kristl et al [33] reported that NH 4 H 2 PO 4 increased nonspecific background absorption, which can be ascribed to the fact that NH 4 H 2 PO 4 thermally stabilizes not only Pb or Cd but also the sample matrix. Therefore, its application cannot be recommended for the determination of Cd and Pb in wine samples.…”
Section: Determination Of Metals In Winementioning
confidence: 98%
“…Therefore, its application cannot be recommended for the determination of Cd and Pb in wine samples. Cr is usually determined in presence of Mg(NO 3 ) 2 [11,13,33], while for As determination, Pd [31] and Ni [5] are used as chemical modifiers.…”
Section: Determination Of Metals In Winementioning
confidence: 99%
“…Among them, 40% of all references are focused on inductively coupled plasma mass spectrometry (ICPMS) [28][29][30][31][32][33] followed by inductively coupled plasma atomic emission spectrometry (ICPAES) [34][35][36][37][38], electrothermal atomic absorption Atomic spectrometry techniques employed for elemental wine analysis (source: Scifinder ® ; Keywords: wine analysis, english, journal, review, 1999, element, atomic absorption, flame, electrothermal, hydride generation, plasma, emission, mass, fluorescence, X-ray). spectrometry (ETAAS) [39][40][41][42][43] and flame atomic absorption spectrometry (FAAS) [19,44,45] with 18%, 16% and 15%, respectively. Then, less popular techniques (i.e.…”
Section: Atomic Spectrometry Techniques For Elemental Wine Analysis: mentioning
confidence: 99%
“…ETAAS has some attractive features since the wine matrix can be partly removed during the pyrolysis step with the aid of chemical modifiers. Among the elements of interest determined by ETAAS are Pb [39,40,42,43,53,64], Cd [39,40,43,64], As [43,65] Sb [65], Al [13], Cu [43], Cr [39], V [15] and Hg [41]. HGAAS/HGAFS techniques are employed for elements such as Pb [50,51,53,66], As [52,66,67], Bi [66], Sn [66], Se [49] and Te [66].…”
Section: Analyte Concentrationmentioning
confidence: 99%